Особливості застосування напірних розподільних трубопроводів у різних технічних системах - Бігун, І. В.; Bihun, Iryna (Видавництво Львівської політехніки, 2019)
Розглянуто основні галузі застосування напірних розподільних трубопроводів дискретним шляховим роздаванням рідини. Це такі галузі: іригація (краплинне, внутрішньоґрунтове й поверхневе зрошення); водопостачання та водовідведення (трубчасті розподільні системи очисних споруд, протипожежні системи); енергетика (охолодження циркуляційної води в атомних і теплових електростанціях (бризкальні басейни та градирні); вентиляція (припливні системи); сільськогосподарська авіація (обприскування рослин); хімічне виробництво; машинобудування (паливні розподільні магістралі багатоциліндрових двигунів внутрішнього згоряння) тощо. Наведено схеми їх влаштування й описано принципи роботи. У довгих розподільних трубопроводах напір уздовж потоку спадає, що спричиняє нерівномірність шляхового роздавання рідини. Однак, у переважній більшості виробничих процесів ставиться завдання забезпечення рівномірного роздавання рідини по усій довжині розподільного трубопроводу. Пошук способів зменшення шляхової нерівномірності роботи розподільних трубопроводів триває. Це актуальна наукова проблема, котру потрібно вирішити, розвиваючи методи розрахунку.

Main fields of application of pressure distributive pipeline are presented. Schemes for construction of distributive pipelines in a range of technological processes and in devices are suggested. Also, the principle of their operation is described. Pressure distributive pipelines with discrete dispensation of fluid along the path are applied in the following spheres: irrigation (sprinkler, subsoil, and surface irrigation); water supply and water removal (tubular distributive systems of purificatory structures, dispersed outlets of purified sewage waters, fire-fighting systems); power engineering (cooling of circulating water in nuclear and thermal power plants (spray ponds and cooling towers) solar collectors); ventilation (tide systems); agricultural aviation (spraying of plants); mechanical engineering (fuel distributive main-pipelines of multi-cylinder internal combustion engines); chemical industry; water transport (distributive systems of water-filling for floodgates and large-sized docks); and others. In long distributive pipelines, there takes place decrease in fluid head along the stream. This causes a decrease in fluid dispensation along the path. In majority of cases of industrial processes, a problem of ensuring of reduction of non-uniformity of fluid dispensation along the whole length of the distributive pipeline arises. The search of ways of reduction of non-uniformity of operation of distributive pipelines still continues. The wide-spread application of enforced streams with variable flow rate fluid flows as well as the absence of reliable techniques of their calculation indicates the urgency of the problem. The authors of this article and those of other publications work on solution of this problem. A way of regulation of fluid dispensation along the path from equipped with nozzles pressure distributive pipelines has been invented. The aim of the author`s works is experimental checking and substantiation of the previously suggested methods for regulating the operation of pressure distributive pipelines.
Peculiarities of application pressure distributive pipelines in different engineering systems
Keywords: напірні розподільні трубопроводи; шляхове роздавання рідини; pressure distributive pipeline; variable flow rate fluid flow